Two-stage leaching of germanium from copper cake under subsequent non-oxidizing and oxidizing conditions - Drzazga, Michal; Kozłowicz, Sylwia; Maj, Izabela; Orda, Szymon; Radoń, Adrian; Ciszewski, Mateusz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Many world economies consider germanium as a critical raw material. Therefore, the development of its recovery from new sources is becoming more and more important. The leaching of copper cake, originating from the purification of zinc electrolyte, in sulfuric acid solution is presented in the paper. The cake contained 24.7% Cu, 21.2% Cd, 16.3% Zn, 4.50% Pb, 3.96% Ni, 3.22% Co and 231 ppm Ge. The leaching of wet and dried material was examined. It was found that the highest germanium recovery was achieved for a two-stage process composed of leaching under non-oxidizing conditions followed by pH adjustment with sodium carbonate followed by oxidizing leaching of residue from the first stage. In the first stage leaching in 12.5% sulfuric acid and later pH adjustment to >2.0 reduced germanium leaching yield to <10%. During oxidizing leaching of remaining residue in 15% sulfuric acid >99% of germanium was leached. The final solution contained 30 mg/dm3 Ge and 72.4 g/dm3 Cu. Germanium may be later recovered from the solution by precipitation with tannic acid or solvent extraction.